Identification of Candidate Transcriptional Regulators of Epidermal Transfer Cell Development in Vicia faba Cotyledons - Arun-Chinnappa, Kiruba S.; McCurdy, David W. (Frontiers in Plant Science, 2016)
Transfer cells (TCs) are anatomically-specialized cells formed at apoplasmic-symplasmic bottlenecks in nutrient transport pathways in plants. TCs form invaginated wall ingrowths which provide a scaffold to amplify plasma membrane surface area and thus increase the density of nutrient transporters required to achieve enhanced nutrient flow across these bottlenecks. Despite their importance to nutrient transport in plants, little is known of the transcriptional regulation of wall ingrowth formation. Here, we used RNA-Seq to identify transcription factors putatively involved in regulating epidermal TC development in cotyledons of Vicia faba. Comparing cotyledons cultured for 0, 3, 9, and 24 h to induce trans-differentiation of epidermal TCs identified 43 transcription factors that showed either epidermal-specific or epidermal–enhanced expression, and 10 that showed epidermal-specific down regulation. Members of the WRKY and ethylene-responsive families were prominent in the cohort of transcription factors showing epidermal-specific or epidermal–enhanced expression, consistent with the initiation of TC development often representing a response to stress. Members of the MYB family were also prominent in these categories, including orthologs of MYB genes involved in localized secondary wall deposition in Arabidopsis thaliana. Among the group of transcription factors showing down regulation were various homeobox genes and members of the MADs-box and zinc-finger families of poorly defined functions. Collectively, this study identified several transcription factors showing expression characteristics and orthologous functions that indicate likely participation in transcriptional regulation of epidermal TC development in V. faba cotyledons.